Acrostic Techniques as an Effort to Increase Motivation And The Ability to Write Poetry VIII Grade Students of SMP14 OKU - Apriliany, Lenny; Wardiah, Dessy; Fitriani, Yessi (Jurnal Pendidikan Tambusai, 2021)
This classroom action research entitled Acrostic Technique as an Effort to Increase the Motivation and Ability to Write Poetry for VIII Grade Students of SMP Negeri 14 OKU. This study involved 24 eighth grade students who have different backgrounds and abilities in writing poetry. By using acrostic techniques, this classroom action research is planned to use two research cycles with a KKM value of 75 and a success rate of above 75%. Based on the results of the data analysis of classroom action research in the first cycle, it was found that the teacher's observation score was very good with a value of 3.33, the value of student observation also reached 62.5% success, and the student's poetry writing score reached 66.6%. In the second cycle, there was a very significant increase. The teacher's observation value increased to 3.55, the student's observation score also increased, making the success rate 100% and the value of writing poetry, all students succeeded in exceeding the KKM score of 75 so that the success percentage was 100%. Thus the classroom action research was declared successful and was stopped in the second cycle. From these results, it can be concluded that acrostic techniques can improve students' ability to write poetry.